Effects of selenium supplementation on concurrent chemoradiotherapy in patients with cervical cancer: A randomized, double-blind, placebo-parallel controlled phase II clinical trial - Yang, Mei; Pei, Bo; Hu, Qiancheng; Li, Xiaoying; Fang, Xiping; Huang, Xue; Yang, Zunjing; Chen, Jiaquan; He, Du; Sun, Guogen; Lv, Peng; Wang, Li; et al. (Frontiers in Nutrition, 2023)
Objective Selenium (Se) is an essential trace element and may affect cervical cancer occurrence and progression. The association between selenium supplementation and acute toxic reactions and clinical outcomes in patients with locally advanced cervical cancer treated with concurrent chemoradiotherapy remains unclear. The aim of this study was to determine the safety profile of add-on Se yeast and assess the potential of Se to ameliorate the hematologic toxicity of concurrent chemoradiotherapy in patients with cervical cancer. Methods Patients with Federation International of Gynecology and Obstetrics (FIGO) stage IIB cervical cancer who met all inclusion criteria were randomly assigned to either the experimental group or the control group. The experimental group received Se yeast tablets (100 μg Se, twice daily), while the control group received placebos (twice daily) for 5 weeks in total. All patients in both groups received standard treatment, including pelvic external irradiation, concurrent five cycles of chemotherapy, and brachytherapy. Measures included the incidence of myelosuppression, impairment of liver and kidney function, objective response rate (ORR), and blood Se concentrations before, during and after the treatment of the two groups. Results A total of 104 eligible patients were enrolled in the experimental group (n = 50) or the control group (n = 54). The ORR in the experimental group and control group were 96 and 94%, respectively (p = 0.47). The baseline levels of blood Se before treatment in the experimental and control groups were similar (58.34 ± 17.63 μg/L and 60.21 ± 18.42 μg/L, p = 0.60), but the concentrations became significantly different after course completion between the two groups (76.16 ± 24.47 μg/L and 57.48 ± 14.92 μg/L, respectively, p < 0.01). Se dramatically decreased the incidence of grade 3 myelosuppression (48% vs. 63%, p = 0.034) compared to the control group. In the subgroup of patients with moderately well-differentiated cervical cancer, the incidence of thrombocytopenia induced by concurrent chemoradiotherapy was lower in the experimental group than in the control group (53.8% vs. 78.9%, p < 0.01). However, no difference was observed in liver and kidney injuries between the two groups. Conclusion Supplementation with Se effectively increased blood Se levels in Se-inadequate cervical cancer patients. As an add-on to standard treatment, Se-yeast significantly decreased the hematologic toxicity of concurrent chemoradiotherapy.